ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL MENGGUNAKAN MODEL INDEKS TUNGGAL PADA PERUSAHAAN YANG TERGABUNG INDEKS KOMPAS 100 DI BURSA EFEK INDONESIA - Ni Made Arik Pebriyanti; I Wayan Widnyana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
This study aims to determine the stocks that will form an optimal portfolio and the amount of proportion on each company shares listed on the Indonesia Stock Exchange (BEI). This research was conducted during January to December 2015 by taking data from stocks - companies that joined in the compass index 100. This study there are 68 companies who become the sample research. Technique of data analysis in this research use Single Index Model. In this study to get the conclusion there are 8 companies that form the optimal portfolio along with the proportion of funds each share in investing. The stocks that make up the optimal portfolio and the proportion of the funds are 22% for UNVR shares, 17% for UNTR shares, 7% for LPKR shares, 2% for SSMS shares, 3% for SMRA shares, 22% for TLKM shares, 17% for ICBP shares , 10% for LPPF.